Investigation of pneumatic transport system of seeding machine "AGRAER-85OH" - V. E. Saitov; R. G. Gataullin (Аграрная наука Евро-Северо-Востока, 2016)
Modem methods of grain production require resource-saving technologies of cultivation of crops. In accordance with the JSC «Malmyzhsky factory for repair of diesel engines» (Russia, Kirov Region) wide-seeding machine «AGRAER-850H» was designed and manufactured. One of the distinguishing features of this unit from existing analogues is the use of pneumatic conveying system for radial fan driven by an internal combustion engine. The aim of research was to determine the aerodynamic characteristics of the generator airflow for the pneumatic system of wide trailer seeding machine. Ventilyator «CRARY» from seeding machine «HORSH Agro-Soyuz» SW 10500 was used as the test generator of air flow on the seeding system. The fan has a diameter of the impeller D2 = 330 mm, wheels working width BK = 65 mm, number of blades z = 44 pcs, blade chordal width b = 25 mm, the blade thickness t = 2 mm. The diameter of the outlet fan is 135 mm, and the entrance window - 250 mm; dimensions of length, width and height, respectively, have the following meanings: 495x152x532 mm. The drive fan is an internal combustion engine «HONDA GX-690" (Japan). Experimental machine made it possible to adjust the air flow by changes in the speed of the crankshaft of the engine and to carry out measurements of the parameters of the air flow. Tests were performed at the fan speed nv of impeller from 3000 to 3700 min-1, which corresponds to the air flow Qv on the outlet pipe of the fan from 2412 to 2960 m3/h. On the investigated range of air flow Qv Nv рower to drive the fan is from 4.25 to 7.98 kW; coefficient of efficiency nv of the fan has a value of 0.453; total pressure Pu is in the range from 2889 to 4395 Pa, and a dynamic pressure Pdu from 1155 to 1739 Pa. A graphic representation of characteristics of an experienced fan and motor «HONDA GX-690» is presented. Comparative analysis of the dependence indicates that the optimum operating range of the centrifugal fan of pneumatic transport system of seeding machine «AGRAER-850H» consistents with the manufacturers recommended operating range of the engine «HONDA GX690». Designed fan can be used with this engine for planting crops in Russia.